Analysis of the Effects of Financial Technologies on Income Improvements of Culinary MSMEs - Dian Nuke Saraswati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy. From a macroeconomic perspective, MSEMs are seen as increasing people's income, reducing poverty levels and opening up job vacancies. However, MSMEs find it difficult to find capital because banking institutions and the government often consider MSMEs not bankable and feasible to finance. This makes MSMEs choose financing from informal institutions. One of the financing models used to support MSMEs is Financial Technology, the type of fintech with the most users, namely Peer to Peer Lending and Digital Payment. The research uses Disruption Theory, Financial Intermediation Theory and Endogenous Growth Theory. The data analysis technique in this study uses the Structural Equation Modeling (SEM) approach, which includes Measurement Model Testing and Structural Modeling Testing. The results of the analysis show that peer-to-peer lending and digital payments have a positive and significant influence on increasing MSME income. This is incited by the t-statistics values ​​of 6.111 and 4.874, specifically, which exceeds the t-table value of 1.96. in addition, the p-value for both variables is 0.000, indicating that both hypotheses in this study are statistically accepted.